STRATEGIC INFORMATION SYSTEMS OF CONSTRUCTION OF FEEDBACK IN HIGHER EDUCATIONAL INSTITUTION - L.M. Alferova (Kherson State University, 2013)
The article is devoted to the construction of a strategic information system of implementing multilevel feedback in higher educational institution. The characteristic of personal criterion for knowledge evaluation was showed. The key principles of feedback construction were outlined. In this article authors provide the analysis of KSU Feedback service using experience in Kherson State University as an example of considered type of a strategic information system.